The Impact of Café Atmosphere, Service Quality, and Interior Design on Customer Loyalty: A Case Study at Lir-Ilir Social House, Genteng, Banyuwangi - Shafirda Rahim (Penerbit Jurnal Indonesia, 2025)
This study aims to examine the impact of café atmosphere, service quality, and interior design on customer loyalty at Lir-Ilir Social House, located in Genteng, Banyuwangi. A quantitative research approach was employed, with data collected through online questionnaires distributed to repeat customers between May 22–28, 2025. The sample was selected using purposive sampling. The measurement of variables used a Likert scale, and the data were analyzed using SPSS version 26, employing validity, reliability, classical assumption tests, multiple linear regression, F-test, and t-test. The results revealed that interior design has a significant positive effect on customer loyalty (sig. = 0.041, p < 0.05), while café atmosphere (sig. = 0.113) and service quality (sig. = 0.824) do not have a significant partial effect. Simultaneously, the three independent variables significantly affect customer loyalty (F = 10.290, sig. = 0.000), with an R Square of 0.499, indicating that 49.9% of the variation in customer loyalty is explained by the model. These findings highlight the importance of aesthetic and functional spatial design in retaining loyal customers. Despite the presence of pleasant ambiance and service quality, interior elements such as layout, cleanliness, lighting, and decorative identity play a more decisive role in shaping customer return intentions. The study provides practical insights for café owners to enhance customer loyalty through interior experience design.